A contribuição da educação musical no ensino integrado integral: um aprendizado para a vida - Carneiro, Rubens Tadeu Passos (2022)
The research has as its theme "The Contribution of Music Education in Integral Integrated Education: A learning for life". It becomes important to understand how Music Education can help in the human formation of the student, especially when related to a curricular matrix that has an inclination towards technical training. What skills and abilities can the Music Education promote in the construction of the individual? Therefore, the investigation has the following objectives: to analyze what is the perception of students in relation to Music Education developed at IFCE; and to understand the formation of the students' musical habitus and the role of Music Education in Integral Integrated Education. For this purpose, the theoretical contribution of Pierre Bourdieu's Praxiology and some of its concepts such as “habitus”, “field” and “agents” are used. In this case study was adopted the methodology through qualitative research, which uses strategies such as narrative and semi-structured interviews. It was analyzed the student's view in relation to music teaching, in the discipline of Art Education, Culture and Music, his musical habitus, cognitive skills that provide access to cultural artistic knowledge, having the omnilateral education as model, integrating specific knowledge with general knowledge. In conclusion, was constated that related activities music education, well with art education discipline, culture and music, this made possible to students purchase competences related critical and reflexive developed skills, work in group, respect to diversity, abilities to dialogue related aspects to technics and theory music languages that help the cultural development and human formation of the student.